1999
DOI: 10.1126/science.286.5440.774
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Dependent Large Accumulation of Point Mutations in the Human mtDNA Control Region for Replication

Abstract: Progressive damage to mitochondrial DNA (mtDNA) during life is thought to contribute to aging processes. However, this idea has been difficult to reconcile with the small fraction of mtDNA so far found to be altered. Here, examination of mtDNA revealed high copy point mutations at specific positions in the control region for replication of human fibroblast mtDNA from normal old, but not young, individuals. Furthermore, in longitudinal studies, one or more mutations appeared in an individual only at an advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
396
2
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 671 publications
(420 citation statements)
references
References 30 publications
18
396
2
4
Order By: Relevance
“…12 On the other hand, examination of mtDNA revealed high numbers of copy point mutations at specific positions in the control region for replication of human fibroblast mtDNA from normal old, but not young, individuals. 13 In cancers, several studies have reported mtDNA alterations. Tamura et al 14 screened for somatic mutations in the mtDNA control region of gastric adenoma and adenocarcinoma and found that 2 of 45 tumors (4%) had mutations in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 On the other hand, examination of mtDNA revealed high numbers of copy point mutations at specific positions in the control region for replication of human fibroblast mtDNA from normal old, but not young, individuals. 13 In cancers, several studies have reported mtDNA alterations. Tamura et al 14 screened for somatic mutations in the mtDNA control region of gastric adenoma and adenocarcinoma and found that 2 of 45 tumors (4%) had mutations in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Some other reports also indicated that the D-loop region (1.1 kb) might be a hot spot for mutations in mtDNA. 13,17 These results prompted us to examine the D-loop region of mtDNA in esophageal cancers. Using detailed sequence analysis, we found that 2 of 37 esophageal cancers (5%) had genetic alterations in this region.…”
Section: Discussionmentioning
confidence: 99%
“…As the damage accumulates, mitochondria lose function. In a 65 year old human about half of the mitochondrial DNA molecules are damaged [7], with a similar loss in mitochondrial respiratory capacity [8].…”
Section: Aging and Diseasementioning
confidence: 99%
“…R ecently, the discovery of an aging-dependent large accumulation of point mutations in the control region for mtDNA replication of human skin fibroblasts has been reported (1). Particularly striking was the demonstration, in a generally high proportion of molecules (up to 50%), of a T to G transversion at position 414 in the original Cambridge sequence (2), within the promoter for the synthesis of the RNA primer of mtDNA heavy (H)-strand synthesis (3) and for light (L)-strand transcription (4).…”
mentioning
confidence: 99%